Uncoupled phytoplankton-bacterioplankton relationship by multiple drivers interacting at different temporal scales in a high-mountain Mediterranean lake - Durán Romero, Cristina (2020)
Global-change stressors act under different timing, implying complexity and uncertainty in the study of interactive effects of multiple factors on planktonic communities. We manipulated three types of stressors acting in different time frames in an in situ experiment: ultraviolet radiation (UVR); phosphorus (P) concentration; temperature (T) in an oligotrophic Mediterranean high-mountain lake. The aim was to examine how the sensitivity of phytoplankton and bacterioplankton to UVR and their trophic relationship change under nutrient acclimation and abrupt temperature shifts. Phytoplankton and bacteria showed a common pattern of metabolic response to UVR × P addition interaction, with an increase in their production rates, although evidencing an inhibitory UVR effect on primary production (PP) but stimulatory on bacterial production (HBP). An abrupt T shift in plankton acclimated to UVR and P addition decreased the values of PP, evidencing an inhibitory UVR effect, whereas warming increased HBP and eliminated the UVR effect. The weakening of commensalistic and predatory relationship between phyto- and bacterioplankton under all experimental conditions denotes the negative effects of present and future global-change conditions on planktonic food webs towards impairing C flux within the microbial loop.